Alexa Rodgers: capstone - Rodgers, Alexa, artist (Colorado State University. Libraries, 2025)
The artist's statement: My work as a graphic designer centers on storytelling, warmth, and visual connection. I am drawn to design that feels personal and inviting, whether through hand-drawn elements, expressive typography, or narrative-driven layouts. Across my projects, I aim to create work that balances thoughtful structure with emotion, allowing design to feel both intentional and human. Illustration and custom type play a central role in my process. In Urban Green, I use hand-drawn imagery and personal typography to explore sustainability through an approachable and organic lens. Rather than presenting environmental messaging as rigid or technical, I focus on softness, movement, and visual rhythm to create a sense of care and accessibility. This approach reflects my broader interest in design that feels lived-in and expressive. Narrative is equally important in my editorial work. Between Cities is a travel magazine that captures moments of transition rather than destinations. Using personal photography and journal-style writing, the project emphasizes pacing, white space, and quiet observation. The design encourages viewers to slow down and engage with the subtle experiences that often go unnoticed, mirroring my own relationship to travel and place. My interest in storytelling extends into brand design as well. Camp Sunshine and Campfire Night is a conceptual retail brand created for Target that focuses on family connection, nostalgia, and shared experiences. Through illustration, color, and adaptable design systems, the project explores how branding can create emotional resonance while remaining functional within a commercial environment. This work reflects my goal of designing for real-world applications without sacrificing visual personality. Together, these projects represent my approach to graphic design as both a communicative and emotional practice. I am interested in creating work that feels warm, thoughtful, and accessible. Designs that invite people in rather than overwhelms them. As I move forward, I hope to continue developing work for brands, publications, and communities that value storytelling, creativity, and meaningful connection.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design